Pemaafan Pelaku Tindak Pidana Pembunuhan Dalam Hukum Islam dan Relevansinya Dengan UU No. 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana - Pebrianto, Roli; Dharma, Muhammad Panji Prabu (Journal of Contemporary Law Studies, 2024)
The debate surrounding the death penalty has been ongoing for a long time with difficult-to-reconcile arguments for and against. Nevertheless, the death penalty still exists in Indonesia's legal system, with several reform efforts including a paradigm shift in sentencing approaches. This study employs normative legal methods to explore the changes in Law Number 1 of 2023, which consider forgiveness for perpetrators of criminal acts, including those sentenced to death. The research findings indicate a shift in criminal law, particularly concerning the death penalty, regulated in Law Number 1 of 2023, especially regarding forgiveness for offenders, even for those sentenced to death. In this regard, Islamic law provides alternative sentencing, including forgiveness from the victim's family as a basis for the abolition of punishment, known in the new Criminal Code as judicial pardon (rechterlijk pardon), both in line with the principles of restorative justice and consistent with Pancasila. In future reforms of Indonesian criminal law, it is hoped that lawmakers will review and adjust other related regulations to align with Law No. 1 of 2023. This adjustment is important to ensure that there are no overlaps or conflicts between existing regulations and the new changes in criminal law. All regulations must be harmonious and support the principles of restorative justice and the values of Pancasila.